2016
DOI: 10.17816/edgcc7213-25
|View full text |Cite
|
Sign up to set email alerts
|

Physical, chemical and biochemical properties of Western Siberia Sphagnum and Carex peat soils

Abstract: Было проведено сравнительное исследование физических, химических и биохимических свойств акротелма (торфогенный горизонт) и катотелма (горизонт накопления торфа) участков с доминированием сфагновых и осоковых торфов в Западной Сибири. Концентрация общего азота прямо пропорциональна содержанию нитрат-ионов и ионов аммония, активности уреазы, объемной плотности, и обратно пропорционально отношению C/N, пористости и влажности в обоих рассматриваемых типах почв. Полученные результаты указывают на низкий уровень аз… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…The field station is a part of the International Network for Terrestrial Research and Monitoring in the Arctic (INTERACT, eu-interact.org) and is actively used by Russian and foreign scientists for studies of the functioning of mire ecosystems. Over the past years, the Mukhrino bog was the main object of numerous experimental study of GHG fluxes (Glagolev et al 2011;Alekseychik et al 2017), geochemistry and physical, chemical, and biochemical properties of peat (Stepanova and Pokrovsky 2011;Szajdak et al 2016), mire hydrology (Bleuten and Filippov 2008), and microbiology including mycology (Filippova et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The field station is a part of the International Network for Terrestrial Research and Monitoring in the Arctic (INTERACT, eu-interact.org) and is actively used by Russian and foreign scientists for studies of the functioning of mire ecosystems. Over the past years, the Mukhrino bog was the main object of numerous experimental study of GHG fluxes (Glagolev et al 2011;Alekseychik et al 2017), geochemistry and physical, chemical, and biochemical properties of peat (Stepanova and Pokrovsky 2011;Szajdak et al 2016), mire hydrology (Bleuten and Filippov 2008), and microbiology including mycology (Filippova et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Elemental composition, atomic ratio, and internal oxidation of studied HA samples are reported in Table 2. The results showed that studied HA samples elemental composition is characteristic for HA isolated from peats (Szajdak et al 2007(Szajdak et al , 2016Huang et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The studies by Szajdak et al (2007Szajdak et al ( , 2016 showed that, the elemental composition of peat humic acids depended on the geobotanical nature of peat.…”
Section: Resultsmentioning
confidence: 99%
“…The third hypothesis is based on the abundance of raised bogs in the middle taiga of WeS [6,7,8,9]. It considers horizontal transport of modern biogenic methane from watersheds peatlands through groundwater to seeps.…”
Section: Introductionmentioning
confidence: 99%